Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jnc.15519
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as a mechanism of neurodegeneration in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia, with complex pathophysiology that is not fully understood. While β‐amyloid plaque and neurofibrillary tangles define the pathology of the disease, the mechanism of neurodegeneration is uncertain. Ferroptosis is an iron‐mediated programmed cell death mechanism characterised by phospholipid peroxidation that has been observed in clinical AD samples. This review will outline the growing molecular and clinical evidence implicating ferroptosis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 328 publications
(390 reference statements)
0
51
0
Order By: Relevance
“…Based on these results, Feng et al concluded that microglial activation after SCI caused ferroptosis of motor neurons and impaired the recovery of motor function [38]. Evidence suggests that ferroptosis is associated with multiple neurologic conditions, making it an increasingly important mechanism of CNS degeneration with microglial activation or polarization [39][40][41]. Consequently, targeting the proferroptosis effect on microglia in the treatment of neural diseases should consider the anti-inflammatory effect as well as the proferroptosis effect to yield optimum results [42].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, Feng et al concluded that microglial activation after SCI caused ferroptosis of motor neurons and impaired the recovery of motor function [38]. Evidence suggests that ferroptosis is associated with multiple neurologic conditions, making it an increasingly important mechanism of CNS degeneration with microglial activation or polarization [39][40][41]. Consequently, targeting the proferroptosis effect on microglia in the treatment of neural diseases should consider the anti-inflammatory effect as well as the proferroptosis effect to yield optimum results [42].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral Fe accumulation in AD was already described in the early 1950s [303]. Lately, Fe accumulation and dyshomeostasis in AD have attracted increasing attention as part of the pathogenesis and as a therapeutic target in recent reviews [304][305][306]. More recent studies of AD brains with advanced techniques (i.a., laser ablation-inductively coupled plasmamass spectrometry) have shown accumulation of Fe in the frontal cortex and hippocampus apparently together with Aβ and p-tau deposits [117,[307][308][309][310][311][312].…”
Section: Iron Accumulation and Pathology In Sporadic Neurodegenerativ...mentioning
confidence: 99%
“…Despite characteristic pathological hallmarks of AD, including Aβ plaque and neurofibrillary tangles, the mechanism of neurodegeneration remains largely obscure. Since phospholipid peroxidation is apparent in AD patient brain samples, a growing body of evidence indicates the involvement of ferroptotic mechanisms in the pathogenesis of AD [ 154 ]. Elevated iron concentration was found in clinic-pathological examinations of AD cases many decades ago and targeting iron has been proposed as a disease-modifying therapy for AD [ 155 ].…”
Section: Ferroptosismentioning
confidence: 99%